2022
DOI: 10.3389/fpsyg.2022.1004297
|View full text |Cite
|
Sign up to set email alerts
|

Work-to-family effects of inclusive leadership: The roles of work-to-family positive spillover and complementary values

Abstract: Drawing on work–family enrichment theory, we explore whether inclusive leadership leads to employees’ work-to-family positive spillover, which further improves their family performance. We also focus on the moderating role of complementary values. A time-lagged study was conducted and the sample included 292 employees from two hotels. The results indicate that inclusive leadership triggers employees’ work-to-family positive spillover, and then their family performance is enhanced. Moreover, employees’ compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Indeed, WFPS is a concept that refers to the transmission of favorable experiences, feelings, and attitudes from the professional environment to the family environment, thus potentially improving the caliber of family connections and general satisfaction in daily existence [65]. In this regard, this concept is associated with a set of variables that drive motivation and improve performance at work [5,66]. Likewise, studies have identified a strong correlation between this variable and the level of autonomy in the workplace; that is, greater control and mastery of work activities leads to possible favorable effects at home [12,67].…”
Section: Fssbs and Work-to-family Positive Spillover (Wfps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, WFPS is a concept that refers to the transmission of favorable experiences, feelings, and attitudes from the professional environment to the family environment, thus potentially improving the caliber of family connections and general satisfaction in daily existence [65]. In this regard, this concept is associated with a set of variables that drive motivation and improve performance at work [5,66]. Likewise, studies have identified a strong correlation between this variable and the level of autonomy in the workplace; that is, greater control and mastery of work activities leads to possible favorable effects at home [12,67].…”
Section: Fssbs and Work-to-family Positive Spillover (Wfps)mentioning
confidence: 99%
“…A positive spillover from work to family encompasses the emergence of positive experiences and emotions in the professional environment, which then exert a favorable influence on the individual's family environment [5]. This issue has aroused the interest of scholars, as both entities and individuals recognize the inherent link between the professional and family spheres.…”
Section: Introductionmentioning
confidence: 99%